Fundamentos bíblicos para liderança cristã protestante em sua atuação na formação de comunidades proféticas e missionais. - Corrêa, Marcos Gaudard (2023)
It is necessary to seek new paradigms for the exercise of leadership in the context of Christian communities according to the countless transformations that the world has undergone. The contemporary world has been identified by four determining factors: Volatility, Uncertainty, Complexity, and Ambiguity (VUCA). Society in general, families, organizations, and Christian communities reflect this scenario; those behaviors require leaders for this time to question their way of acting and develop the qualities, styles, and skills necessary to discover opportunities for changes and growth. These elements will also help them face the challenges that lie before them. Behind a crisis, there can be a great opportunity. The opportunity will be well-taken advantage of if there is a willingness to learn, innovate, and reinvent processes, organizations, and especially themselves, always considering the Holy Scriptures as a reference. Biblical leaders of the past can positively inspire leadership in their contemporary communities. For this reason, four biblical characters recognized in the biblical tradition were selected for the present investigation. There were prominent men in the leadership of God's people at different times in history: Moses, the liberator, who led the people of Israel from their departure from Egypt to their entry into the land of Canaan; the same one who delivered the law that would serve to distinguish Israel from the other peoples of Palestine; David, the greatest king in history, the reference for the other kings of Israel; Elijah, the great prophet who marked the history of prophetism in Israel; and John the Baptist, sent by God to prepare the way for the Messiah, the one who became the first prophetic voice of the New Testament. These leaders present leadership foundations that point to Jesus, the best leadership reference in the Holy Scriptures. The four characters analyzed are given as reference, despite the limitations, mistakes, and successes. Christians consider Jesus Christ the paramount leader of all times; He has much to teach and inspire leaders with his leadership style. Jesus developed a prophetic, priestly guidance, according to the values of the kingdom of God. His leadership was also disciple-making, servant, and pastoral. During his ministry on Earth, he presented the foundations that became leadership references for the world. Careful re-reading of the Scriptures (especially the Gospels) allows the leader to study and apply Jesus' leadership style and foundations, which offer inspiration for the search for answers to current challenges. Some of these challenges are the formation of prophetic and missional contemporary Christian communities. Reviewing, combined with listening to the signs of the times and the community’s needs, will contribute to the search for new clues for leadership that is a sign of the Kingdom of God in the world.